Family Mediation in Resolving Conflicts Arising from Toxic Behavior in the Online Game Mobile Legends: A Conceptual Analysis and 5M Model Based on Tahkīm and Sulh - Revi Mariska; Yoki Pradikta, Hervin; Mu'in, Fathul (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to examine the characteristics of family conflicts arising from toxic behavior in the competitive online game Mobile Legends: Bang Bang (MLBB) and to formulate a family mediation strategy based on the principles of Islamic Family Law, particularly sulh and tahkīm. The study employs a qualitative approach with an empirical descriptive-analytical design through the integration of literature review, conceptual legal analysis, and synthetic case illustrations to enhance analytical depth and theoretical coherence. The findings indicate that family conflicts are primarily triggered by competitive pressure and the phenomenon of online disinhibition during gameplay, which subsequently extends into the domestic sphere in the form of emotional tension, neglect of family responsibilities, and financial disputes due to in-game expenditures. These findings underpin the formulation of the 5M Family Mediation Model, which consists of mapping problems, managing emotions, conducting deliberation, establishing agreements, and monitoring as well as evaluating outcomes. The model emphasizes the importance of empathetic communication, emotional regulation, structured limitations on gaming duration and spending, as well as the reinforcement of islāḥ and tahkīm values as mechanisms for just and sustainable conflict resolution. This study contributes conceptually to the discourse on digital behavior and family mediation within the framework of Islamic law, although it is limited by its illustrative nature and the absence of primary empirical field data. This condition opens opportunities for future empirical studies to test the effectiveness of the proposed model across broader and more diverse social contexts.